ANALYSIS OF THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS (EMR) IN THE OUTPATIENT INSTALLATION OF ERNALDI BAHAR HOSPITAL, SOUTH SUMATRA PROVINCE - Herlenni Evi Sesty; Akhmad Dwi Priyatno; Erma Gustina; Syahrizal; Zuhro Haris (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
The problems that often occur are the repair of the Health Information System (SIMRS) with 50 cases and issues related to the local area network (LAN) with 34 cases. The use of Electronic Medical Records (RME) in the Outpatient Installation of RS Ernaldi Bahar has not yet improved the waiting time for services in the clinic. In addition, healthcare workers still need to fill out manual medical record forms. The research employed a qualitative descriptive study approach. The research was conducted from May 20, 2025, to June 10, 2025. The informants in this study consisted of 8 respondents who played a role in the implementation of electronic medical records (RME) using purposive sampling techniques. Data collection was carried out using interviews, observations, and documentation. Based on the research findings, it was found that the availability of facilities and infrastructure is almost 100%, although the common problem is disruptions in internet connectivity. Human resources are still insufficient, but all personnel have participated in socialization and RME training; however, the use of RME is more dominated by the younger age group. Regulations and guidelines are already available electronically in the SIMRS application. The RME interface is user-friendly but still needs improvement according to the hospital's needs.